Chronic adaptations of lung function in breath-hold diving fishermen - Cristiane Diniz; Tiago Farias; Mayane Pereira; Caio Pires; Luciana Gonçalves; Patrícia Coertjens; Marcelo Coertjens (International Journal of Occupational Medicine and Environmental Health, 2014)
Objectives: The aim of this study was to verify and analyze the existence of chronic adaptations of lung function in freediving fishermen whose occupation is artisanal fishing. Material and Methods: This was a cross-sectional study involving 11 breath-hold diving fishermen and 10 non-breath-hold diving fishermen (control) from the village of Bitupitá in the municipality of Barroquinha (Ceará - Brazil). Anthropometric measurements, chest and abdominal circumferences as well as spirometric and respiratory muscle strength tests were conducted according to the specifications of the American Thoracic Society/European Respiratory Society (ATS/ERS). In order to compare the measured values versus the predicted values, Student t test was used in the case of parametric test and Wilcoxon test in the case of nonparametric test. To compare the inter-group means Student t test was used for parametric test and Mann-Whitney test for the nonparametric one. The level of significance was set at α = 5%. Results: The forced vital capacity (FVC) (4.9±0.6 l vs. 4.3±0.4 l) and forced expiratory volume in 1 s (FEV1) (4.0±0.5 l vs. 3.6±0.3 l) were, respectively, higher in the group of divers compared to the control group (p ≤ 0.05). Furthermore, in the group of free divers, the measured FVC, FEV1 and FEV1/FVC ratios were significantly greater than the predicted ones. No differences were found between the measured respiratory pressures. Conclusions: These results indicate that breath-hold diving seems to produce chronic adaptations of the respiratory system, resulting in elevated lung volumes with no airway obstruction.